Research progress on ferroptosis in the pathogenesis and treatment of neurodegenerative diseases - Wang, Lijuan; Fang, Xiansong; Ling, Baodian; Wang, Fangsheng; Xia, Yu; Zhang, Wenjuan; Zhong, Tianyu; Wang, Xiaoling (Frontiers in Cellular Neuroscience, 2024)
Globally, millions of individuals are impacted by neurodegenerative disorders including Huntington's disease (HD), amyotrophic lateral sclerosis (ALS), Parkinson's disease (PD), and Alzheimer's disease (AD). Although a great deal of energy and financial resources have been invested in disease-related research, breakthroughs in therapeutic approaches remain elusive. The breakdown of cells usually happens together with the onset of neurodegenerative diseases. However, the mechanism that triggers neuronal loss is unknown. Lipid peroxidation, which is iron-dependent, causes a specific type of cell death called ferroptosis., and there is evidence its involvement in the pathogenic cascade of neurodegenerative diseases. However, the specific mechanisms are still not well known. The present article highlights the basic processes that underlie ferroptosis and the corresponding signaling networks. Furthermore, it provides an overview and discussion of current research on the role of ferroptosis across a variety of neurodegenerative conditions.